The Phenomenon of Recharging the Soul: An Analysis of Tafsir Al-Mishbah on the Spiritual Needs of Gen Z - Abbas, Faiz Musthofa; Almufassir, A Zamzami; Ali Hamdan; Adib Rofiuddin Basori (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract Generation Z, having grown up in the digital age, faces significant psychological challenges, including increased anxiety, depression, and identity crises. While contemporary psychological frameworks address these issues, they often lack the spiritual dimension crucial for holistic well-being among Muslim youth. Therefore, this study investigates the integration of Tafsir Al-Mishbah by M. Quraish Shihab with the recovery theory by Sonnentag and Fritz (2007), specifically focusing on the mental and spiritual well-being of Generation Z. By using a qualitative approach with descriptive-interpretative analysis, this study illustrates how Shihab's contextual interpretation of the Qur'an provides a robust spiritual framework for managing modern psychological pressures. The research demonstrates that the four dimensions of recovery—psychological detachment, relaxation, mastery, and control—can be deeply aligned with Islamic practices. Specifically, these dimensions correspond to prayer (sholat), remembrance of Allah (dhikr), the obligation to seek knowledge, and managing leisure time according to Sharia principles. The findings suggest that integrating spiritual practices with contemporary recovery theory can significantly foster emotional resilience, offering a comprehensive approach to mental health recovery that encompasses both psychological and spiritual dimensions. Keywords: Generation Z; Islamic spirituality; Mental health; Recovery theory; Tafsir Al-Mishbah. Abstrak Generasi Z, yang tumbuh di era digital, menghadapi tantangan psikologis yang signifikan, termasuk peningkatan kecemasan, depresi, dan krisis identitas. Meskipun kerangka psikologis kontemporer berupaya mengatasi masalah ini, pendekatan tersebut sering kali kehilangan dimensi spiritual yang sangat penting bagi kesejahteraan holistik pemuda Muslim. Oleh karena itu, penelitian ini menyelidiki integrasi Tafsir Al-Mishbah karya M. Quraish Shihab dengan teori recovery oleh Sonnentag dan Fritz (2007), dengan fokus khusus pada kesejahteraan mental dan spiritual Generasi Z. Dengan menggunakan pendekatan kualitatif dan analisis deskriptif-interpretatif, studi ini menggambarkan bagaimana tafsir kontekstual Shihab terhadap Al-Qur'an memberikan kerangka spiritual yang kuat untuk mengelola tekanan psikologis modern. Penelitian ini menunjukkan bahwa empat dimensi pemulihan—psychological detachment, relaksasi, mastery, dan kontrol—dapat diselaraskan secara mendalam dengan praktik Islam. Secara spesifik, dimensi-dimensi tersebut berkorespondensi dengan ibadah shalat, dzikir (mengingat Allah), kewajiban menuntut ilmu, dan pengelolaan waktu luang yang sesuai dengan prinsip syariah. Temuan penelitian ini menunjukkan bahwa mengintegrasikan praktik spiritual dengan teori recovery kontemporer dapat meningkatkan ketahanan emosional secara signifikan, serta menawarkan pendekatan pemulihan kesehatan mental yang komprehensif mencakup dimensi psikologis dan spiritual. Kata Kunci: Generasi Z; Kesehatan mental; Spiritualitas Islam; Tafsir Al-Mishbah; Teori recovery.